(untitled) (Baltic Journal of Sport and Health Sciences, 2018)
The aim of the study was to establish the impact of hyperthermia and dehydration on maximum voluntary contraction (MVC) force and central fatigue, as well as to assess the impact of rehydration on the function of skeletal muscle in conditions of hy- perthermia when performing isometric exercise of maximum intensity for 2 minutes. The subjects were adult females (n = 8) not actively engaged in sports, aged 21.2 ± 2.4 years, body mass — 64.84 ± 8.4 kg and height — 170.8 ± 2.5 cm respectively. Three studies were carried out: one control study and two experimental ones. During the ﬁ rst experiment the bodies of the participants in the study were subjected to hyperthermia and dehydration (the subjects sat immersed up to the pelvis in hot water (44 ± 1 o C) bath for 45 min). During another experiment, the same methods of increasing hyperthermia being used, the bodies of the subjects experienced oral rehydration with 1000 ml NaCl 0.9% solution of 37 o C. The MVC load lasted for 120 s (MVC-2 min) and every 15 s the muscle was stimulated by electrical impulses: the duration of the stimulation was 250 ms, the frequency — 100 Hz and the voltage — 85—105 V accordingly. We registered the movement of MVC (N * m) and the degree of voluntary activation of muscles according to the formula VA% = (MVF + electrical im- pulse) / MVF * 100. When the load was applied the subjects were motivated verbally and they were provided with the visual feedback of changes in force signals. After hyperthermia and dehydration was applied, the rectal body temperature increased from 37.48 ± 0.25 to 39.5 ± 0.23 o C (p < 0.001), and the inner temperature of the muscle (3 cm deep) — from 36.91 ± 0.29 to 39.83 ± 0.31 o C (p < 0.001) on the average. During the hyperthermia experiment the subjects had lost 0.4 ± 0.07 kg in weight on the average, and that was 0.62 ± 0.13% of their body mass. After oral rehydration in conditions of hyperthermia body mass of the subjects had increased by 0.48 ± 0.01 kg on the average, i. e. by 0.74 ± 0.08% of their body mass. Having analyzed the physiological index of heat stress (in the 10-point system) we have found that during both experiments the subjects had experienced a physiological stress of an extremely high level, e. g. in the case of hyperthermia — 8.85 ± 1.13 points and in the case of rehydration — 8.38 ± 0.98 points respectively. There was a signiﬁ cant decrease (p < 0.001) in MVC at the 3rd second of the load during both experimental researches and control research — at the 15th second of the load. These changes in MVC remained until the end of the 2nd min, compared to the indices registered before the load. During recovery, 5 min (A 300) after the load applied, MVC during control and experimental (hyperthermia) research had regained the level registered be- fore the load (p > 0.05). Two-factor dispersion analysis revealed that the changes in the force in this case depended on time (p < 0.001), as well as on the body state (p = 0.001), whereas interaction of time and body state had no signiﬁ cant effect on the result (p > 0.05). After the analysis of the indices of voluntary activation we noticed that hyperthermia (p < 0.05) and rehydration (p < 0.01) had signiﬁ cantly increased the degree of voluntary activation (VA%), compared to the one established before the load. During the recovery time, 15 s after the load had been undertaken, the force index of voluntary activation regained the level that had been registered before the load. Two-factor dispersion analysis allowed us to establish that the changes in the force indices of voluntary activation depended on time (p < 0.001), the body state (p = 0.047) and the interaction between them (p < 0.05). Applying the methods of passive muscle heating the participants in the study were subjected to hyperthermia and 1 o dehy- dration. Hypertension increased the central fatigue. During the experiments of hyperthermia and dehydration MVC force fatigue altered homogeneously. In conditions of hyperthermia, rehydration had a negative impact on the central fatigue and increased it even more when maximum isometric load for 2 min had been undertaken. Keywords: hyperthermia, isometric exercise, dehydration, rehydration, central fatigue.